Éléments d’archéologie du bâti pour une histoire de la boucherie francilienne contemporaine (Val-de-Marne, Seine-Saint-Denis) - Jean-Yves Dufour (Revue Archéologique du Centre de la France)
The surveys carried out in two Ile-de-France farms and two village butchers plunge us into the heart of the history of contemporary Ile-de-France butcher. To meet the ever increasing demand for meat, the population of Paris and its suburbs, agricultural establishments observed at Sucy-en-Brie and La Queue-en-Brie, transformed their traditional buildings into intensive cattle breeding places. These animals were slaughtered in Paris, or in village 'slaughter houses'. At Orly, a large barn, a chicken coop, a slaughter house, a rendering plant and attics are spread around the courtyard of a village butcher. The archival work informs us of the presence of a butcher's shop at least since the early nineteenth century. In Neuilly-sur-Marne, the butcher's shop has closed, leaving all its instruments on site. Behind his shop and his town house, the construction study revealed a slaughter house, a cold room, a cooler, a shed and a place for stabling spread around a courtyard. The archival study also reveals continuous slaughter activity from the beginning of the nineteenth century. Not constrained by the division of labour observed in central Paris in the nineteenth century, these suburban butchers may have preserved old work techniques. Their study should help us to better distinguish the slaughter places among our medieval remains.